Light-weight Umbilical Cable Design - NIU Xuechao; LU Jianjia; CHEN Ziwei; XIE Shuhong; GU Chunfei; SUN Jie; Chen Zhenzhen; MAO Bing (Guangtongxin yanjiu)
【Objective】The umbilical cable is one of the core pieces of equipment for marine scientific exploration. It typically uses high-strength steel wires as the load-bearing elements. However, steel wires have a high density, and as the operating water depth increases, the proportion of the umbilical cable's own weight in the safe working load also increases, reducing the safety margin for ultra-deep water applications. Therefore, there is a need for lightweight design of umbilical cables.【Methods】The light-weight umbilical cable replaces steel wires entirely with low-density, high-hardness aramid Fiber Reinforced Polymer Compsite Materials (FRP) in its innermost layer. In the middle layer, steel wires are partially replaced at intervals, while the outermost layer maintains a full steel wire structure to enhance overall wear resistance and facilitate heat dissipation through the gaps in the loadbearing layer when seawater seeps in. To mitigate interlayer wear, a wear-resistant layer is extruded on the surface of the FRP, thereby increasing its fatigue resistance for long-term use.【Results】Firstly, compared with steel wire umbilical cables, light-weight umbilical cables reduce the unit weight by 30.50% in air and 37.29% in seawater, and increase the static water depth by 27.6%, expanding the application scenarios of umbilical cables. Secondly, the finite element method is used to analyze and compare the stiffness, tensile strength, and heat dissipation performance of lightweight umbilical cables and steel wire umbilical cables. It is found that the tensile stiffness of lightweight umbilical cables is 16.7% lower and the bending stiffness is 20.0% lower. Both types of cables can reach the theoretical fracture tensile load, and the stress of both materials is less than the fracture strength. At this time, the elongation of the cables is 1.45%. Under the same current in seawater, the temperature of the light-weight umbilical cable core is 0.7 ℃ higher, which is 2.9% higher than the steel wire umbilical cable. Finally, the prototype cable was manufactured and subjected to tensile tests based on common failure modes, as well as tests for fatigue under alternating loads and tension-bending fatigue. The test results confirm that after 2 000 cycles of fatigue, the lightweight umbilical cable still has high strength and minimal interlayer wear.【Conclusion】Under the premise of unchanged outer diameter, lightweight umbilical cables can significantly increase the application water depth. Two different load-bearing materials with different characteristics can simultaneously exert maximum tensile performance. Through testing, it has been verified that the lightweight umbilical cables have high reliability.